Positive Periodic Solutions of Functional Difference Equations and Applications in Population Dynamics (Journal of Nonlinear Modeling and Analysis, 2024)
In this work, we discuss the existence of positive periodic solutionsfor nonlinear functional difference equations. We illustrate the applicability ofour main result by examining the Lasota–Wazewska, the Mackey–Glass andthe Nicholson’s Blowflies models.